Update on non-bismuth quadruple (concomitant) therapy for eradication of Helicobacter pylori - Gisbert, Javier P (Dove Medical Press, 2012)
BACKGROUND: Traditional standard triple therapy for Helicobacter pylori (H. pylori) infection (proton pump inhibitor-clarithromycin-amoxicillin) can easily be converted to non-bismuth quadruple (concomitant) therapy by the addition of a nitroimidazole twice daily. AIM: To critically review evidence on the role of non-bismuth quadruple therapy (proton pump inhibitor-clarithromycin-amoxicillin-nitroimidazole) in the treatment of H. pylori infection. METHODS: Bibliographical searches were performed in MEDLINE and relevant congresses up to December 2011. We performed a meta-analysis of the studies evaluating the concomitant therapy, and of the randomized controlled trials comparing the concomitant and the standard triple therapy. RESULTS: A meta-analysis of 19 studies (2070 patients) revealed a mean H. pylori cure rate (intention-to-treat) of 88% (95% confidence interval from 85% to 91%) for non-bismuth quadruple therapy. We performed a meta-analysis of the randomized controlled studies comparing the concomitant (481 patients) and the standard triple therapy (503 patients). The former was more effective than the latter: 90% versus 78% (intention-to-treat analysis). Results were homogeneous (I(2) = 0%). The odds ratio for this comparison was 2.36 (95% confidence interval from 1.67 to 3.34). A tendency toward better results with longer treatments (7–10 days versus 3–5 days) has been observed, so it seems reasonable to recommend the length of treatment achieving the highest cure rates (10 days). Clarithromycin resistance may reduce the efficacy of non-bismuth quadruple therapy, although the decrease in eradication rates seems to be far lower than in standard triple therapy. Experience with the non-bismuth quadruple therapy in patients with metronidazole-resistant strains is still very limited. CONCLUSION: Non-bismuth quadruple (concomitant) therapy appears to be an effective, safe, and well-tolerated alternative to triple therapy and is less complex than sequential therapy. Therefore, this regimen appears well suited for use in settings where the efficacy of triple therapy is unacceptably low.